CDK12/13 inhibition overcomes platinum resistance by impairing RNA metabolism - Ilenia Pellarin; Valentina Rossi; Riccardo Giuseppe Margiotta; Javad Karimbayli; Alessio Polacchini; Ashwani Bahl; Milena Nicoloso; Maura Sonego; Sara D’Andrea; Laura Sala; Simone Canesi; Andrea Favero; et al. (Signal Transduction and Targeted Therapy, 2026)
Abstract Epithelial ovarian cancer (EOC) is a highly lethal disease characterized by a high rate of platinum (PT)-resistant recurrence. Dysregulation of transcriptional and alternative splicing (AS) has been suggested as a possible mechanism of PT resistance involving transcriptional cyclin-dependent kinases (CDKs). We report that pharmacological CDK12/CDK13 inhibition (CDK12i) synergistically enhances PT-induced cytotoxicity in a large number of PT-sensitive and PT-resistant EOC models. CDK12i effectively delayed the emergence of PT-resistant recurrences in vitro and in vivo. Acquired resistance to CDK12i enhanced PT sensitivity, revealing a therapeutically exploitable vulnerability to PT. CDK12i strongly reshapes transcriptional elongation and RNA processing, impacting multiple categories of AS, with marked enrichment of transcripts involved in the DNA damage repair (DDR) pathway. We proved that CDK12 interacts with the splicing master regulator SFPQ/p54 nrb complex, driving its distribution in transcriptional condensates. The p54 nrb subunit of the complex is required for the CDK12-SFPQ interaction and to ensure splicing reprogramming and CDK12i-induced cytotoxicity in all the EOC models tested. The use of CT7439, a novel clinical-grade CDK12i, which is now in phase I/II clinical trials, confirmed the therapeutic potential of CDK12i, either as monotherapy or in combination with PT. These findings emphasize that the therapeutic potential of CDK12i extends beyond DDR regulation, encompassing a critical role in RNA processing and AS. This dual impact affects EOC survival and may provide a novel, clinically relevant therapeutic strategy for hard-to-treat PT-resistant patients for whom effective treatment options remain limited.